The high diversity of gametogenic pathways in amphispermic water frog hybrids from Eastern Ukraine - Pustovalova, Eleonora; Choleva, Lukaš; Shabanov, Dmytro; Dedukh, Dmitrij (PeerJ, 2022)
Interspecific hybridization can disrupt canonical gametogenic pathways, leading to the emergence of clonal and hemiclonal organisms. Such gametogenic alterations usually include genome endoreplication and/or premeiotic elimination of one of the parental genomes. The hybrid frog Pelophylax esculentus exploits genome endoreplication and genome elimination to produce haploid gametes with chromosomes of only one parental species. To reproduce, hybrids coexist with one of the parental species and form specific population systems. Here, we investigated the mechanism of spermatogenesis in diploid P. esculentus from sympatric populations of P. ridibundus using fluorescent in situ hybridization. We found that the genome composition and ploidy of germ cells, meiotic cells, and spermatids vary among P. esculentus individuals. The spermatogenic patterns observed in various hybrid males suggest the occurrence of at least six diverse germ cell populations, each with a specific premeiotic genome elimination and endoreplication pathway. Besides co-occurring aberrant cells detected during meiosis and gamete aneuploidy, alterations in genome duplication and endoreplication have led to either haploid or diploid sperm production. Diploid P. esculentus males from mixed populations of P. ridibundus rarely follow classical hybridogenesis. Instead, hybrid males simultaneously produce gametes with different genome compositions and ploidy levels. The persistence of the studied mixed populations highly relies on gametes containing a genome of the other parental species, P. lessonae.
Keywords: Bivalents; sperma; Humans; Anura; Amphispermy; Spermatid; In Situ Hybridization, Fluorescence; žáby; Ukrajina; gametogeneze; Gametogenesis; Meiosis; lidé; zvířata; Hybridogenesis; Male; hybridizace in situ fluorescenční; Semen; Pelophylax; Animals; Ukraine; mužské pohlaví; FISH